2000
DOI: 10.1038/sj.bmt.1702478
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of γδ T cell repertoire diversity after human allogeneic hematopoietic cell transplantation and the role of peripheral expansion of mature T cell population in the graft

Abstract: Summary:We have examined the reconstitution of ␥␦ T cell repertoire diversity after human allogeneic hematopoietic cell transplantation using a polymerase chain reaction (PCR)-based complementarity-determining region (CDR) 3 size spectratyping and DNA sequencing. The CDR3 complexity in the variable region of the T cell receptor (TCR)-␦ chain was different amongst the individuals studied. Furthermore, CDR3 size distribution patterns of allogeneic hematopoietic cell transplant recipients were almost completely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 45 publications
(36 reference statements)
0
40
0
Order By: Relevance
“…47 The predominant mechanism of gd reconstitution seems to be peripheral expansion of donor gd clones, which can persist for more than 1.5 years after transplantation. 48 Unlike ab T cells, gd T cells can reconstitute via an alternative, thymusindependant pathway. 49,50 However, the precise regulatory and cytotoxic functions of gd T cells after transplantation are not fully understood, and further investigation is required to define the role and importance of gd T cells as potential targets for post transplantation immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…47 The predominant mechanism of gd reconstitution seems to be peripheral expansion of donor gd clones, which can persist for more than 1.5 years after transplantation. 48 Unlike ab T cells, gd T cells can reconstitute via an alternative, thymusindependant pathway. 49,50 However, the precise regulatory and cytotoxic functions of gd T cells after transplantation are not fully understood, and further investigation is required to define the role and importance of gd T cells as potential targets for post transplantation immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 We also found that TCR usage appears to be limited, and that amino acid sequences frequently contain an arginine residue followed by acidic amino acid residues in the complementarity-determining region 3 (CDR3) of TCR-␤ chains containing BV24S1, suggesting that skewing of the TCRAV and TCRBV repertoires is antigen-driven. 1 These features of post-transplant T cell regeneration are similar to those during extrathymic differentiation of T cell progenitors and peripheral expansion of mature T cell populations, which have been demonstrated by murine bone marrow transplantation studies.…”
mentioning
confidence: 94%
“…The PCR products of the TCR-␤ chain were cloned into the PCR2.1 TA cloning vector (Invitrogen, Carlsbad, CA, USA) and sequenced using a Big-Dye Terminator Cycle Sequencing Kit (Perkin-Elmer Applied Biosystems) 3 and an Applied Biosystems 377A automated DNA sequencer.…”
Section: Sequencing Cdr3 Regions In Tcr-␤ Chainsmentioning
confidence: 99%
“…Studies also reveal TCR gd T cells can be classified into Th1 cells and Th2 cells. In the different stages of respiratory allergic inflammation, different TCR gd T cells exert positive or negative regulatory effects on the immune function, and specific immunotherapy (SIT) can rectify the imbalance between T cell subsets (3)(4)(5)(6)(7)(8). The knowledge on TCR gd T cells is still insufficient as compared to TCR ab T cells, and few studies report the role of TCR gd T cells in allergic rhinitis (AR) and SIT.…”
Section: Introductionmentioning
confidence: 99%
“…Ten AR patients undergoing SIT with house-dust-mite extract for 1 year were recruited. Quanti tative analysis of immunofluorescence was performed to detect the serum specific IgE (sIgE) level before and after SIT; RT-PCR-genescan analysis was employed to detect the mRNA expressions of TCR Vg (I-III) and Vd (1)(2)(3)(4)(5)(6)(7)(8) in the peripheral mononuclear cells followed by analysis of T cell clonality. Real-time quantitative PCR was applied to detect the expressions of TCR Vg I-III genes.…”
mentioning
confidence: 99%